Quantitative easing and sovereign yield spreads : Euro-area time-varying evidence - Afonso, António (2022)
We assess the determinants of sovereign bond yield spreads in the period 1999:01– 2016:07, considering non-conventional monetary policy measures in the Euro area. We use a 2-step approach to: (i) confirm and estimate the determinants of sovereign bond yield spreads; (ii) compute bivariate time-varying coefficient (TVC) models of each determinant and analyse the temporal dynamics. The baseline determinants of sovereign bond yield spreads in the Euro area are the bid-ask spread, the VIX, fiscal developments and rating developments, REER, and economic growth. QE measures implemented by the ECB in the aftermath of the crisis are also relevant. From the TVC analysis, the Covered Bond Purchase Programme contributed to reduce yield spreads, particularly in the 2011–2013 period. Longer-term refinancing operations contributed to reduce yield spreads in most countries..